Environmental factors are an important part of farmers’ assessments of the value of agroecology - Coe, Ric; Andrieu, Nadine; Alary, Véronique; Ky-Dembele, Catherine; Magaju, Christine; Orounladji, Boko Michel; Vall, Eric; Sinclair, Fergus (Frontiers in Sustainable Food Systems, 2025)
The need for transformation of food and agriculture systems to be aligned with sustainable development goals is widely acknowledged. Evidence from many parts of the world shows that agroecology, which considers the social and environmental performance of agricultural systems along with economic aspects, is helping farmers transition to sustainable agricultural systems. However, there are demands from national, regional and international food and agriculture planners and funders for evidence that agroecology can work at scale. Providing that evidence requires understanding how farmers use environmental factors when selecting agricultural practices, which is poorly documented. This study contributes to filling this gap by reporting how environmental factors are important in farmers’ decisions related to adopting agroecological practices. Qualitative and quantitative data from 239 key informants, a survey of 5025 farms, 85 focus group discussions with farmers and five participatory cross-benefit analyses in eleven case studies across eight African countries were used. We show that farmers use information on and perceptions of a wide range of environmental variables and processes when assessing the usefulness of agroecological practices. In most cases, farmers cited environmental factors more frequently than economic reasons for choosing to use agroecological practices. Most of the environmental factors articulated by farmers were components of the local or farm environment that were connected to their livelihood, including aspects of soils, water, microclimate, pests and diseases, other animals, and vegetation. Intrinsic and relational environmental values such as conservation of biodiversity, long-term maintenance of land quality and aesthetics were also important. These findings show first that providing data on environmental roles of agroecology will always be challenging because of the breadth of factors that are important. Secondly, viability or usefulness of an agroecological practice is not a characteristic of the practice alone, but also of the context in which it is used. Third, impact analyses of agroecological interventions cannot be confined to consideration of a few globally comparative indicators but need to include the context specific environmental factors that farmers care about.